Questioning the Clinical Utility of Exome Sequencing in Developing Countries. Issue 1 (22nd November 2016) - Fong, Kenneth; Bailey, Celeste V.; Tuttle, Peggy; Cunningham, Bari; McGrath, John A.; Cho, Raymond J.
Abstract: The availability of whole‐exome sequencing has revolutionized the study of genetic disease in recent years, particularly in dermatology, where clinical phenotypes are readily recognized. As this technology becomes increasingly affordable and accessible, questions are emerging regarding the clinical and ethical responsibilities of physicians who determine variants underlying disease, especially with regard to children, for whom treatment may be warranted and clinical course improved based on a known genotype. These responsibilities are accentuated in the developing countries, which harbor most consanguineous populations and thus bear the brunt of monogenic genodermatoses. Although many genetic disorders are identified in these populations, limited educational and clinical infrastructure rarely offers opportunities to improve the course of disease. Here we report a genetic study that illustrates these challenges.